Jorgelina Corbatta. Narrativas de la Guerra Sucia en Argentina : Piglia, Saer, Valenzuela, Puig. Buenos Aires : Corregidor, 1999. 174 p. - Fabry, Geneviève (Nueva Revista de Filología Hispánica (NRFH), 2001)
Se reseñó el libro: Narrativas de la Guerra Sucia en Argentina : Piglia, Saer, Valenzuela, Puig.